Resveratrol impacts health in patients with diabetes mellitus and other metabolic conditions - Emilia Nowak; Dominika Psiuk; Agata Rocka; Natalia Dycha; Patryk Jasielski; Faustyna Jasielska; Dominika Madras; Ewelina Rocka (Kazimierz Wielki University, 2022)
Background Resveratrol is a polyphenol with many properties, including activity against glycation, oxidative stress, inflammation, neurodegeneration, carcinogenesis and aging. It appears to be a promising compound for the prevention and treatment of metabolic diseases. The aim of this review is to summarize the results of the latest clinical trials that concern effects of resveratrol in diabetes mellitus type 1 and 2 and its complications - diabetic foot ulcers, diabetic nephropathy and non-alcoholic fatty liver disease.   Aim of the study Based on in vitro studies and animal models, it has been observed that resveratrol reverses the factors causing premature death: obesity, hypertension, and hyperlipidemia. Because of its anti-inflammatory, antioxidant, cardioprotective and blood lowering glucose effects, it appears to be a promising compound for the treatment of metabolic conditions. The review presents different clinical trials concerning the efficiency of resveratrol supplementation in patients with diabetes mellitus and metabolic syndrome and their complications. Most studies focused on assessing the effect of resveratrol supplementation as an adjunctive treatment of diabetes mellitus type 2 and in this group of patients it gave the best results causing reduction of fasting glucose levels, fasting insulin concentration, insulin resistance and improvement of insulin sensitivity and lipid profiles.   Conclusions Resveratrol remains a potential drug in the treatment of metabolic diseases like diabetes mellitus. However, the results of the conducted trials are inconscient. More research is needed to confirm the effectiveness of resveratrol supplementation in treating diabetes, its complications and other metabolic conditions.